Gesture errors in left and right hemisphere damaged patients: A behavioural and anatomical study. (12th November 2021) - Scandola, Michele; Gobbetto, Valeria; Bertagnoli, Sara; Bulgarelli, Cristina; Canzano, Loredana; Aglioti, Salvatore Maria; Moro, Valentina
Abstract: Objective: Erroneous gesture execution is at the core of motor cognition difficulties in apraxia. While a taxonomy of errors may provide important information about the nature of the disorder, classifications are currently often inconsistent. This study aims to identify the error categories which distinguish apraxic from non-apraxic patients. Method. Two groups of mixed (bucco-facial and limb) and bucco-facial apraxic patients suffering from stroke were compared to non-apraxic, left and right hemisphere damaged patients in tasks tapping the ability to perform limb and bucco-facial actions. The errors were analysed and classified into 6 categories relating to content, configuration or movement, spatial or temporal parameters and unrecognisable actions. Furthermore, an anatomical investigation (VLMS) was conducted in the whole group of left hemisphere damaged patients to investigate potential correlates of the various error categories. Results. Although all the above error typologies may be observed, the most indicative of mixed apraxia is the content-related one in all the typologies of actions (transitive and intransitive), and configuration errors in transitive ones. Configuration and content errors in mouth actions seem to be typical of bucco-facial apraxia. Spatial errors are similar in both apraxic and right brain damaged, non-apraxic patients. A lesion mapping analysis of left-brain damaged patients demonstrates that all but the spatial error category are associated with the fronto-parietal network. Moreover, content errors are also associated with fronto-insular lesions and movement errors with damage to the paracentral territory (precentral and postcentral gyri). Spatial errors are often associated to ventral frontal lesions. Conclusions. Bucco-facial and mixed apraxic patients make different types of errors in different types of actions. Not all errors are equally indicative of apraxia. In addition, the various error categories are associated with at least partially different neural correlates. Highlights: Not all gesture errors identify apraxia. Content and configuration errors are specific to apraxia. Spatial errors are not specific to apraxia. Different Neural substrates underpins different gesture errors. Gesture errors are different in apraxic and non-apraxic patients.